Named Data Networking (NDN), New Approach to Future Internet Architecture Design: A Survey - Zain ul Abidin Jaffri; Zeeshan Ahmad; Muhammad Tahir (Institute of Advanced Engineering and Science, 2013)
To envision and evolve the Internet into the future, what required is a simple but a vital architectural modification which focuses on “What (the contents)” rather than “Where (the addresses)”, that the Internet users and the applications are more concern about. So the communication can be more in effect if the customers can simply identify that what content they want to have instead of from where the content can be possessed. To achieve this and also to make the system more efficient and effective, new internet architecture emerged which we baptized as “Named Data Networking” or simply “NDN” in which packets bring with it the hierarchical data names instead of carrying the source and destination address. In NDN when the customer needs some data, he sends the interest packet which carries the name, is first received by the router and the router then forwards it as per instructed by FIB and uphold the status of pending interest , in further which is used for guiding the retrieved data back to the customer. The main objectives behind developing this architecture are to bring the scalability, efficiency, security and robustness in the current internet state, facilitating the user choice and competition as well. In this paper an overview of different future internet architectural approaches are provided such as CCN, NetInf, PRISP and DONA. NDN as a brand new architectural design among them remains the leading focus and its altered architectural design as a source of fulfilling the above mentioned major issues and objectives.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.5122